7‐Tesla Magnetic Resonance Imaging for Brain Iron Quantification in Homozygous and Heterozygous PANK2 Mutation Carriers. Issue 4 (23rd October 2014) - Dusek, Petr; Tovar Martinez, Elena Maria; Madai, Vince Istvan; Jech, Robert; Sobesky, Jan; Paul, Friedemann; Niendorf, Thoralf; Wuerfel, Jens; Schneider, Susanne A.
Abstract Pantothenate‐kinase–associated neurodegeneration (PKAN) is an autosomal recessive disorder characterized by iron deposits in basal ganglia. The aim of this study was to quantify iron concentrations of deep gray matter structures in heterozygous PANK2 mutation carriers and in PKAN patients using quantitative susceptibility mapping MRI. By determining iron concentration, we intended to find mutation‐specific brain parenchymal stigmata in heterozygous PANK2 mutation carriers in comparison to age‐matched healthy volunteers. We studied 11 heterozygous PANK2 gene mutation carriers (mean age: 43.4 years; standard deviation [SD]: 10.5), who were found to be clinically asymptomatic by neurological examination. These carriers were compared to 2 clinically affected PKAN patients 21 and 32 years of age and to 13 age‐matched, healthy controls (mean age: 39.7; SD, 13.6). Scanning was performed on a 7.0‐Tesla whole‐body scanner applying three‐dimensional susceptibility‐weighted gradient echo acquisitions. Susceptibility maps were calculated by threshold‐based k‐space division with single‐orientation acquisition. Magnetic susceptibility values, relative to the occipital white matter, were determined for the following regions of interest (ROI): globus pallidus (GP), thalamus, putamen, internal capsule (IC), caudate nucleus, substantia nigra (SN), and red nucleus. Heterozygous PANK2 mutation carriers did not show increased brain iron concentrations, compared to healthy controls (P > 0.05), in any of the examined ROIs. In PKAN patients, more than 3 times higher concentrations of iron were found in the GP, SN, and IC. Our results suggest that heterozygous mutations in PANK2 gene do not cause brain iron accumulation nor do they cause movement disorders.